Recording of Marriage Agreements and Consequences for Third Parties - Endah Hartati; Lauditta Humaira (Journal of Social Research, 2025)
In recent years, the demand for Marriage Agreements has increased among couples planning to marry, as it allows them to regulate the property consequences of their marriage. The Marriage Law requires that these agreements be made prior to marriage; however, Constitutional Court Decision Number 69/PUU-XIII/2015 has opened the possibility of creating postnuptial agreements after marriage, a practice that has gained popularity. Despite this, a significant issue remains in the implementation of postnuptial agreements, particularly regarding the lack of regulation on publicity. This research explores the challenges surrounding the principle of publicity in Marriage Agreements and examines the implications of a third party's right to refuse the implementation of a postnuptial agreement. The study uses a normative legal research method, analyzing relevant legal texts and case law. The findings indicate that the absence of clear regulations on publicity leads to uncertainties about the enforceability and legal protection of postnuptial agreements, particularly in relation to third-party interests. This paper suggests that clearer legal provisions are needed to address the issue of publicity, ensuring better legal certainty and protection for all parties involved in postnuptial agreements.